AKUNTABILITAS PENGELOLAAN ALOKASI DANA DESA PADA DESA PINGGIR AIR - Setiawan, Rafika Gina; Rahayu, Sri; Rahayu, Rahayu; Sam, Iskandar (Widya Mandala Surabaya Catholic University, 2021)
Research Purposes. This study aims to explore the accountability of the management of village fund allocations (ADD), how effective and efficient the allocation of village funds is, and how much the contribution of village fund allocations to Pinggir Air Village, Kumun Debai District, Sungai Penuh City.Research Methods. Primary data collection techniques in this study using a questionnaire distributed to respondents. Secondary data collection techniques in this study using budget realization reports (LRA). Respondents in this study were village officials and community figures totaling 30 respondents.Research Result and Findings. The result shows that the rate of accountability for managing the ADD at Pinggir Air Village has been very good where the planning to accountability stages have been implemented properly. Level of effectiveness and efficiency realization of ADD on Pinggir Air Village has been effective and efficient. Realization of ADD on Pinggir Air Village in accordance with ADD target and the realization of spending from the use of Village Funds is efficient, 99.64% of village funds are allocated and implemented according to the planned use and do not exceed the realization of village income. Contribution rate realization of ADD on Pinggir Air Village reaches 100%. This means that the level of dependence on village funds is very high.